Changes in the diet of the predatory ribbonfish Trichiurus lepturus Linnaeus, 1758 with increasing body size along Chennai coast - Gomathy, S.; Vivekanandan, E. (Indian Journal of Fisheries, 2018)
In recent years, it has been recognised that predatory fishes are rapidly declining in marine habitats. Hence, gathering information on biological characteristics such as dietary dynamics of predatory fishes has assumed importance. Considering this, the dietary dynamics of the predatory ribbonfish Trichiuruslepturusfrom Chennai coast was assessed by analysing the stomach condition and contents, with reference to body size. Representatives of the Order Clupeiformes (Index of relative importance, IRI 33.7%) comprising oilsardine, lesser sardines and anchovies were the major prey items of T. lepturus. Predation by T. lepturus was aided by morphological adaptations, such as dentition, hard and spinous gill rakers, short stomach, high body depth-total length ratio of 1: 17.1 and large mouth (gape area of 1534 mm2 in adult fish).With increasing body size, the capacity to predate upon relatively larger prey increased. The differences in diet composition between ribbonfish of small, medium and large size were well-represented byIRI, prey specific abundance and cluster analysis. The fish is a top predator (trophic level: 4.17) and a specialist feeder (niche breadth: 2.63). As specialist feeders have a narrow choice of food, they are more vulnerable to fishing. It is important that management of multispecies fisheries should focus more on the sensitive predatory species.